2019
DOI: 10.1002/adma.201905111
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoint: From Responsive to Adaptive and Interactive Materials and Materials Systems: A Roadmap

Abstract: toward higher levels of complexity and takes increasing inspiration from the concepts of living species, it feels imminent and of high importance to foster the discussion on this topic and provide a roadmap to evolve synthetic systems from responsive to adaptive and interactive systems and materials. This is not only important in the context of highlighting landmark advances of future systems over present ones, but also relevant for the education of the next generation of researchers going to operate in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
221
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 260 publications
(225 citation statements)
references
References 58 publications
0
221
0
4
Order By: Relevance
“…Living organisms have evolved into a system that can response and adapt to the change of environment to better fulfill their survival tasks. 1 Inspired by Nature's elegant way, biomimetic designs have been very fruitful for creating robust artificial structures with distinct sensitivities to various stimuli. 2,3 While these smart materials show a great promise for generating highly intelligent and efficient devices, [4][5][6] most of them are based on a closed system, which only allows energy transfer but prohibits substance exchange with surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…Living organisms have evolved into a system that can response and adapt to the change of environment to better fulfill their survival tasks. 1 Inspired by Nature's elegant way, biomimetic designs have been very fruitful for creating robust artificial structures with distinct sensitivities to various stimuli. 2,3 While these smart materials show a great promise for generating highly intelligent and efficient devices, [4][5][6] most of them are based on a closed system, which only allows energy transfer but prohibits substance exchange with surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…[261] An emerging concept in the soft materials field is the development of adaptive and interacting networks, which are designed to better mimic complex spatiotemporal responses found in biological systems. [262] Furthermore, it is becoming increasingly clear that hydrogel-encapsulated cells actively deposit nascent proteins which can significantly alter the nature of the cell-material interface. [263,264] For example, Horton et al recently showed that mesenchymal stem cells encapsulated in PEG hydrogels www.afm-journal.de www.advancedsciencenews.com…”
Section: Discussionmentioning
confidence: 99%
“…The final system will be able to react to certain triggers, adapt to the environment, and harvest energy to maintain its homeostasis, implying that the energy demand of the actuation systems is lower or equal to the provided energy from the harvester and storage structures. In order to attain this, materials are needed that are able to sense, react, and adapt to the environment (Walther, 2019). These should be able not only to adapt but also to learn and to transition from one stable energy state to another.…”
Section: Envisioning a True Avft As An Inspiration For Living Adaptivmentioning
confidence: 99%